HUBUNGAN PENERAPAN KEWASPADAAN TERHADAP OBAT HIGH-ALERT DENGAN KEJADIAN MEDICATION ERRORS DI MURNI TEGUH MEMORIAL HOSPITAL MEDAN - Lady Noveline Sofiani Pasaribu; Seriga Banjarnahor (Jurnal Riset Multidisiplin Edukasi, 2025)
Background: Medication error is any preventable event, that in inappropriate medication use (harm to the patient) when the medication is under the control of the health care professional, patient, or consumer. The classification of medication errors includes prescribing errors, dispensing errors, medication preparation errors, administration errors, and monitoring errors. High-alert drugs are drugs that have a high risk of causing major harm to patients if not used appropriately. High-alert drugs are several drugs that can harm patients if the drug is used incorrectly. The general principles for handling high-alert drugs are storage, prescribing, drug preparation/distribution, and drug administration. The most effective treatment for high-alert drugs is by reducing errors in administering high-alert drugs. To monitor high-alert drugs, "high alert" must be given. Method: This research uses quantitative research methods using a correlational design. Sampling used the Slovin formula with a total sample of 138 respondents, sampling from the population using proportional random sampling techniques. The research instrument used was a questionnaire sheet. The data analysis used was Spearman's rho test. Results: The results of the study show that there is a relationship between the application of alertness towards high-alert drugs and the incidence of medication errors at Murni Teguh Memorial Hospital. The Spearman's rho test shows a p-value of 0.001 (<0.05). Conclusion: There is a relationship between the implementation of high-alert medication awareness and the incidence of medication errors at Murni Teguh Memorial Hospital.